Full-Length Transcriptome Analysis Reveals Candidate Genes Involved in Terpenoid Biosynthesis in Artemisia argyi - Cui, Yupeng; Gao, Xinqiang; Wang, Jianshe; Shang, Zengzhen; Zhang, Zhibin; Zhou, Zhenxing; Zhang, Kunpeng (Frontiers in Genetics, 2021)
Artemisia argyi is an important medicinal plant widely utilized for moxibustion heat therapy in China. The terpenoid biosynthesis process in A. argyi is speculated to play a key role in conferring its medicinal value. Yet the molecular mechanism underlying terpenoid biosynthesis remains unclear, in part because the reference genome of A. argyi is unavailable. Moreover, the full-length transcriptome of A. argyi has yet to be sequenced. Therefore, in this study de novo transcriptome sequencing of A. argyi’s root, stem and leaf tissues was performed to obtain those candidate genes related to terpenoid biosynthesis, by combining the PacBio single-molecule real-time (SMRT) and Illumina sequencing NGS platforms. These respectively generated more than 55.4 Gb of sequencing data and 108,846 full-length reads (non-chimeric) were generated by the Illumina and PacBio platform, respectively. Then, 53,043 consensus isoforms were clustered and used to represent 36,820 non-redundant transcripts, of which 34,839 (94.62%) were annotated in public databases, namely those of Nr, eggNOG, GO, Swiss-Prot, KEGG, and Pfam. A differential gene expression analysis that compared A. argyi leaves with root and stem tissues revealed 13,850 (7,566 up-regulated, 6,284 down-regulated) and 9,502 (5,284 up-regulated, 218 down-regulated) uniquely assembled transcripts as differentially expressed (DETs) between them. Specifically, the expression profile and KEGG functional enrichment analysis of these DETs indicated that they were significantly enriched in the biosynthesis of amino acids, carotenoids, diterpenoids and flavonoids, as well as the metabolism processes of glycine, serine, and threonine. Moreover, multiple genes encoding significant enzymes or transcription factors related to diterpenoid biosynthesis were highly expressed in the A. argyi leaf tissue. Additionally, several transcription factor families, such as RLK-Pelle_LRR-L-1 and RLK-Pelle_DLSV, were also identified. In conclusion, this study offers a valuable resource for transcriptome information, providing a functional genomic foundation for further research on molecular mechanisms underlying the medicinal use of A. argyi leaves.